Effects of trampoline training on jump, leg strength, static and dynamic balance of boys - (:unkn) unknown (My University, 2013)
The purpose of this study is to examine the effects of 12-week trampoline training on static- dynamic balance, vertical jump and leg strength parameters in boys who do not exercise regularly. Twenty-eight 9-to10-year old boys were assigned to the trampoline training group (TG, N=15) and control group (CG, N=13) to examine effects of 12-week trampoline training (TT) on leg strength (LS), vertical jump (VJ), static balance (SB) and dynamic balance (DB). TG was given 12-week training, whereas no sport activities were assigned to CG. According to our results, differences between the pre-test and post-test bipedal SB, VJ, DB in TG are statistically significant (p<0.05). No significant difference was observed between the pre and post-test results in terms of unipedal SB, LS. Whereas in the CG, there was no significant difference between pre-test and post-test results based on any of the performance parameters (p>0.05). 12-week trampoline training increased bipedal SB-DB and VJ parameters; however, it had no effect on unipedal SB and LS parameters in boys. The trampoline training used in our study may form an example for the sports educators for improving strength and balance in children.
Keywords: Children; Muscle strength; Postural balance; Power; Trampoline training